Who has it? a probit analysis of entrepreneurship. - Tay, Richard Soon Teck. (2008)
This report consists of four papers on entrepreneurship: (1) an ordinal probit analysis of entrepreneurship, (2) determinants of entrepreneurial career choice among university graduates in Singapore, (3) tertiary education, gender and entrepreneurship: an empirical analysis, (4) persuasive communications in the venture process: an exploratory study.